(untitled) (Environment & Health, 2019)
The low doses of irradiation cause a destructive effect not only on the organism but also on the subsequent generations of its offspring Objective: We determined the mechanisms of in vivo radioprotective and radiocorrective effects of dietary phytoadditive of milled milk thistle fruits on the systems of hydrolysis and transport of carbohydrates of various degrees of polymerization in a small intestine of the offspring of one-time irradiated male rats. Materials and methods: A single exposure of male rats was performed with a help of teletherapy gamma-apparatus "AGAT-R-1". A dose rate was 120 rad/min, a field - 20×20, a distance from the source of irradiation to the field - 75 cm, a dose - 0.5 Gy, an exposure time - 32 sec. Accumulating mucosa preparation (AMP) was produced by the Ugolev method [9]. AMP was incubated for an hour at t=37ºC in oxygenated medium. The solutions of 10 mmol/l of glucose or 5 mmol/l of maltose, made on the Ringer solution with pH 7.4, were used as an incubation medium. 3 drops of rabbit bile were added for emulsification into all media. Concentration of glucose was established by the colorimetric method with the help of photoelectrocolorimeter – CFC-2МP, λ= 625 nm. We assessed the activity of the transport of free and M-glucose in the AMP of the offspring of irradiated male rats under various conditions of the use of milk thistle by the parents. Results: The dietary additive of milled fruits of milk thistle causes a stimulation of the transport both free and M-glucose (1.6-fold in relation to the intact groups in both cases) in the offspring of irradiated male rats that got the thistle before irradiation and intact female rats (radioprotective effect), and respectively 2.7-fold and 2.8-fold in the offspring of irradiated hungry male rats through female rats that were consuming the thistle during lactation (radiocorrective effect). Conclusions: The dietary additive of milled fruits of milk thistle causes the radioprotective and radiocorrective effects in the offspring of the first generation of irradiated males. Realization of both effects has the gender features: radioprotective effect is realized through irradiated fed male rats that got thistle before irradiation and intact female rats but radiocorrective effect is realized in the offspring of irradiated hungry male rats through female rats that were consuming the thistle during lactation.